2014
DOI: 10.1093/brain/awu224
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in VCP causes Charcot–Marie–Tooth Type 2 disease

Abstract: Mutations in VCP have been reported to account for a spectrum of phenotypes that include inclusion body myopathy with Paget's disease of the bone and frontotemporal dementia, hereditary spastic paraplegia, and 1-2% of familial amyotrophic lateral sclerosis. We identified a novel VCP mutation (p.Glu185Lys) segregating in an autosomal dominant Charcot-Marie-Tooth disease type 2 family. Functional studies showed that the Glu185Lys variant impaired autophagic function leading to the accumulation of immature autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 21 publications
3
102
0
2
Order By: Relevance
“…1A). Many, but not all, previously reported pathogenic VCP mutations have enhanced basal ATPase activity [24]. To test this, we measured the basal rate of ATP hydrolysis in the presence of recombinant wild-type VCP (VCP-WT), VCP-I27V, VCP-R95C and the most common pathogenic VCP mutation VCP-R155H.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). Many, but not all, previously reported pathogenic VCP mutations have enhanced basal ATPase activity [24]. To test this, we measured the basal rate of ATP hydrolysis in the presence of recombinant wild-type VCP (VCP-WT), VCP-I27V, VCP-R95C and the most common pathogenic VCP mutation VCP-R155H.…”
Section: Resultsmentioning
confidence: 99%
“…Purified recombinant VCP-WT and VCP variants were assayed for intrinsic ATPase activity as previously described [24]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in VCP have been associated with dissimilar clinical manifestations, including hereditary inclusion body myopathy (IBM) with PDB and early onset FTD (IBMPFD),30 ALS,31 hereditary spastic paraplegia32 and Charcot-Marie-Tooth disease type 2 33. In the present study, we have found the missense p.I27V variant in a patient with a definitive diagnosis of lower MND with accompanying argyrophilic grains and mild AD-pathology, which may justify the clinical bvFTD syndrome as no classical FTLD pattern was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, detailed family history should be taken before the genetic test in order to determine the inheritance pattern and to possibly identify similar phenotypes in other family members. As much as possible clinical information should be recorded, even if it seems unrelated to the neuromuscular symptoms observed in the index case, since mutations in the same gene can have varying phenotypic presentations [68]. Thorough search for extramuscular presentations should also be performed for the patient and other family members, as certain rare genetic disorders can have other symptoms in addition to those related to myopathy [69].…”
Section: Determining the Pathogenicity Of An Identified Variantmentioning
confidence: 99%